An anesthetized rat assay for evaluating the effects of organophosphate-based compounds and countermeasures on intracranial EEG and respiratory rate - Thinschmidt, J. S.; Harden, S. W.; Talton, J. D.; Frazier, C. J. (Frontiers in Drug Discovery, 2024)
The development of medical countermeasures (MCMs) against organophosphate (OP) induced poisoning is of substantial importance. Use of conventional therapeutics is complicated by offtarget effects and restricted penetration of the blood-brain barrier (BBB). Therefore, a concerted effort is underway to discover improved acetylcholinesterase (AChE) reactivators, muscarinic acetylcholine receptor (mAChR) antagonists, and other countermeasures with broader spectrum activity and enhanced CNS efficacy. We recently developed a rat brain slice assay to assess the efficacy of AChE reactivators and mAChR antagonists against the acute effects of the organophosphorus AChE inhibitor 4-nitrophenyl isopropyl methylphosphonate (NIMP) in the basolateral amygdala (BLA). Here we introduce a complimentary anesthetized animal model to evaluate the same compounds in vivo with concurrent monitoring of EEG and respiratory rate. We find that intravenous delivery of 0.5 mg/kg NIMP reliably produces seizure like activity in the BLA, with concurrent respiratory depression and eventual respiratory failure. The central effects of AChE reactivators and mAChR antagonists delivered intravenously are consistent with their expected ability to cross the BBB. Combining our previously described in vitro assay with the methods described here provides a relatively comprehensive set of preclinical tools for evaluating the efficacy of novel MCMs. Notably, using these methods potentially obviates subjecting conscious animals to cholinergic crises, which aligns with the AAALAC's 3Rs principle of refinement.